Modern Methods of Treating Chronic Periodontitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Periodontal disease is a chronic disease of the tissues around the tooth (gum, bone tissue, ligaments, cementum). According to the WHO, half of the world's population, approximately 3.5 billion people, suffer from periodontal disease. Therefore, timely and correct treatment is important.